2013
DOI: 10.1111/bju.12346
|View full text |Cite
|
Sign up to set email alerts
|

Deformity stabilization and improvement in men with untreated Peyronie's disease

Abstract: Objective To define predictors of the deformity stabilisation and improvement in men with untreated Peyronie's disease (PD). Patients and Methods The study population consisted of patients with PD‐associated uniplanar curvature, who opted for no treatment and were followed for at least 12 months. All patients had deformity assessment (DA) performed on initial presentation and at follow‐up. Stabilisation of PD was defined as no change between DAs (±10°), while improvement and progression were defined as ≥10°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Nevertheless, available previous placebo -controlled studies [7] show a maximum angle reduction of 21% with Impress I and of 15.2% for the placebo group. Furthermore, the comparison of our results with those of untreated patients, as in Berookhim's trial [17] conducted on 176 patients to study the natural history of PD in the absence of medical or surgical therapy, further supports a beneficial effect of the combination of PRP and HA, as only 12% of untreated patients had an improvement of their deformation vs 62% in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, available previous placebo -controlled studies [7] show a maximum angle reduction of 21% with Impress I and of 15.2% for the placebo group. Furthermore, the comparison of our results with those of untreated patients, as in Berookhim's trial [17] conducted on 176 patients to study the natural history of PD in the absence of medical or surgical therapy, further supports a beneficial effect of the combination of PRP and HA, as only 12% of untreated patients had an improvement of their deformation vs 62% in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…61 Berookhim et al reported a 12% improvement rate in untreated men with uniplanar PD, with time to presentation of ≤ 6 months and younger age as predictors of improvement. 62 Perhaps more significantly, 67% of men in this cohort remained stable, and 21% worsened during the follow-up period of at least 12 months. Another study observed a 30% progression rate in 307 men with PD over 8 months, with resolution occurring in only 0.65% of cases.…”
Section: Natural History and Presentationmentioning
confidence: 69%
“…In 1743, Francois Gigot de la Peyronie's wrote a landmark article on PD, and his name was associated with the disease. Despite this long history, there are no medical or surgical therapies 10 and there is a paucity of knowledge on the natural history of PD, although deformity stabilization and improvements in specific subsets of men with untreated PD have recently been reported 11 …”
Section: Introductionmentioning
confidence: 99%